HTML5 games most wanted - Kuryanovich, Egor (Apress, 2012)
HTML5 Games Most Wanted gathers the top HTML5 games developers and reveals the passion they all share for creating and coding great games. You'll learn programming tips, tricks, and optimization techniques alongside real-world code examples that you can use in your own projects. You won't just make gamesyou'll make great games. The book is packed full of JavaScript, HTML5, WebGL, and CSS3 code, showing you how these fantastic games were built and passing on the skills you'll need to create your own great games. Whether you're a coding expert looking for secrets to push your games further, or a beginner looking for inspiration and a solid game to build on and experiment with, HTML5 Games Most Wanted is for you. Topics and games covered include building complexity from simplicity in A to B, how to create, save, and load game levels in Marble Run, creating fast 3D action games like Cycleblob, entity interpolation from Snowball Fight, trait-based gaming in Grave Danger, the advanced use of WebGL from the game Bar Fight, tips on combining the entangled web of HTML5 technologies brilliantly shown in Far7, the holy grail of making a unique game like Z-Type, and how to build split-screen games as in the addictive Robots Are People Too.